Effects of hydrogenation and aging on the optical properties in porous Si layers - Oh, Do-Hyun; Lee, Soojin; Cho, Woon-Jo; Kim, Tae Whan (SPRINGER, 2007)
The effects of hydrogenation and aging on the optical properties in porous Si (PS) layers were investigated by using photoluminescence (PL) measurements. When the hydrogenated PS layers were aged in air, the intensity of the PL spectrum increased. The emission peak for the hydrogenated PS layers shifted to higher energy with decreasing H-2/N-2 ratio. The relation of the dehydrogenized states in the as-formed PS surface to the quantum states of Si nanoparticles with relatively small sizes is discussed. These results indicate that the optical properties of PS layers are significantly affected by hydrogenation and aging.
Keywords: PHOTOLUMINESCENCE; PASSIVATION